2007
DOI: 10.1002/jhm.212
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in hospitalized patients treated with antihyperglycemic agents

Abstract: OBJECTIVE:To determine the incidence and manifestations of hypoglycemia in hospitalized patients receiving antihyperglycemic therapy. RESEARCH DESIGN AND METHODS:The study was a 3-month prospective review of consecutive medical records of all adult, nonpregnant hospitalized patients at a 675-bed university hospital who experienced at least 1 blood glucose (BG) Յ 60 mg/dL within 48 hours of receiving an antihyperglycemic agent. MEASUREMENTS AND RESULTS:Of 2174 patients receiving antihyperglycemic agents, 206 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 22 publications
1
65
1
2
Order By: Relevance
“…This phenomenon is well documented on the inpatient treatment. One study reported that 40% of hospitalized patients had recurrent episodes of hypoglycemia, 22 while in another study severe hypoglycemic episodes were preceded by mild hypoglycemia in more than 60% of cases. 23 Another factor favoring a dysregulation of the counter is the [page 12] [Italian Journal of Medicine 2015; 9:549] presence of autonomic neuropathy.…”
Section: Risk Factors Of Hypoglycemiamentioning
confidence: 99%
“…This phenomenon is well documented on the inpatient treatment. One study reported that 40% of hospitalized patients had recurrent episodes of hypoglycemia, 22 while in another study severe hypoglycemic episodes were preceded by mild hypoglycemia in more than 60% of cases. 23 Another factor favoring a dysregulation of the counter is the [page 12] [Italian Journal of Medicine 2015; 9:549] presence of autonomic neuropathy.…”
Section: Risk Factors Of Hypoglycemiamentioning
confidence: 99%
“…Intraoperative blood glucose concentrations should be measured no less frequently than hourly. Patients with abnormal kidney function should be identified preoperatively since there is a greater incidence of perioperative hypoglycemia in these patients [43,44] .…”
Section: Outpatient Diabetes Managementmentioning
confidence: 99%
“…Hypoglycemia is a common problem in diabetic patients treated with insulin and can induce various neurological disturbances, such as confusion, motor restlessness, hypotonia, and epileptic seizures, which represent a relatively common acute symptom (41,70). The association between hypoglycemia and epilepsy or seizures has not yet been fully understood.…”
Section: Seizures and Glycemic Variationsmentioning
confidence: 99%